High-strength and high-elasticity silk fibroin-composite gelatin biomaterial hydrogels for rabbit knee cartilage regeneration - Ma, Hebin; Xie, Bowen; Chen, Hongguang; Song, Puzhen; Zhou, Yuanbo; Jia, Haigang; Liu, Jing; Zhao, Yantao; Zhang, Yadong (Frontiers in Materials, 2024)
Suitable hydrogel materials for cartilage tissue repair should exhibit high strength and toughness, and excellent biocompatibility. However, the mechanical properties of most hydrogels cannot meet the complex mechanical requirements of articular cartilage tissues. Given this situation, we have adopted a chemical cross-linking method using hexafluoro isopropanol (HFIP) to mediate the cross-linking of Silk Fibroin (SF) and deionized water (DI), which promoted the formation of β-sheets, generating "high-toughness" SF hydrogels. The introduction of Gelatin (Gel) served to increase the content of βsheets and increase the tensile modulus from 24.51±2.07 MPa to 39.75±6.54 MPa, which significantly enhanced the flexibility of the hydrogel and meets the mechanical requirements of cartilage tissue. In addition, in vitro biological experiments have shown that the introduction of Gel promotes cell proliferation and enhances the production of cartilage extracellular matrix (ECM) by chondrocytes. In vivo experiments have demonstrated that SF/Gel hydrogel promotes articular cartilage regeneration more effectively than SF hydrogel, as evidenced by improvements in gross appearance, imaging, and histology. This study has established that high-strength SF/Gel hydrogel prepared by applying the binary-solvent-induced conformation transition (BSICT) strategy has potential applications in cartilage tissue repair and regeneration and is a feasible biomaterial for osteochondral regeneration.